Graphene perfect absorber design based on an approach of mimicking a one-port system in an asymmetric single resonator - Lee, Sangjun; Song, Joohyung; Kim, Sangin (Optics Express, 2021)
We proposed a novel perfect absorber with an asymmetric single resonator supporting two degenerate resonant modes, whose operation concept is mimicking a one-port system by making only one of the modes experience loss while using the other for an internal 100% reflector in conjunction with the background scattering. We confirmed the operation principle and the design requirement from a theoretical study using the temporal coupled-mode theory. We also designed an example device based on the guided-mode resonances (GMRs) in a slab-waveguide grating and numerically demonstrated a high absorption of ∼ 99.95% in monolayer graphene with greatly enhanced fabrication error tolerance in comparison to the previously proposed scheme. Our proposed scheme will find various useful applications due to the intuitive design process and relatively easier fabrication, which is attributed to the one-port mimicking operation concept with a single GMR-based broadband flat-top reflector.
Keywords: Coupled mode theory; Design process; Fabrication errors; Guided-mode resonance; Perfect absorber; Resonant mode; Slab waveguides; Theoretical study